Evaluation of the procoagulant properties of a newly developed platelet modified lysate product. Issue 7 (15th May 2020) - Refaai, Majed A.; Conley, Grace W.; Hudson, Chad A.; Spinelli, Sherry L.; Phipps, Richard P.; Morrell, Craig N.; Blumberg, Neil; McRae, Hannah L.
Abstract : BACKGROUND: Platelet transfusion is associated with logistical problems with the national storage guidelines of platelets. This results in decreased function in vivo as a result of the platelet storage lesion, and complications such as allergic or hemolytic reactions and thrombosis. We evaluated a new, freshly prepared platelet modified lysate (PML) product designed to be more procoagulant than fresh and stored platelets. METHODS: Fresh platelets were concentrated, sonicated, and centrifuged to produce PML. Samples of both washed and unwashed PML were evaluated for particle size, concentration, and activity, and then tested for clot kinetics and thrombin generation. PML samples were also stored at various temperatures for durations up to 6 months and evaluated for clot kinetics and thrombin generation throughout. RESULTS: PML showed significantly higher concentration of platelet microparticles, increased procoagulant properties, and increased thrombin generation as compared to fresh and stored platelets. In addition, PML maintained its clot kinetics over a 6‐month storage period with variable storage conditions. CONCLUSIONS: The newly proposed PML product is more procoagulant, stable, and has additional potential applications than currently available platelet products. Further studies will be performed to assess its functions in vivo and to assess thrombotic potential.